2022
DOI: 10.5985/emcr.20210012
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in new unexposed and beached expanded polystyrene foams

Abstract: Among the plastic debris surveyed in the marine environment, a large quantity in terms of volume was found to be expanded polystyrene foam (EPS). This is due to its light weight and popularity as a packaging material. In this study, 28 compounds of polycyclic aromatic hydrocarbon (PAHs) were analyzed in both new and beached EPS collected in California, USA. In beached EPS, a variation in total PAH concentrations of up to 2 orders of magnitude was observed in the 337 to 11,800 ng / g-EPS range. Meanwhile, new E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To contextualize the PAH content of the spilled plastic, we compared our results to the PAH content measured and reported in the literature from 19 studies of plastic pellets (317 data points) and 15 studies of plastic debris (198 data points) found globally in the marine environment (Figure ). ,, When they arrived onshore on May 25, 2021, the white nurdles had an EPA16 PAH content (∼1260 ng/g) double the median for nurdles found globally in the marine environment (∼589 ng/g). It should be noted that many of these other studies examined nurdles with a yellowness index of 30 to 50, assuming that the yellowing indicated that these nurdles had been in the environment long enough to accumulate significant amounts of PAHs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To contextualize the PAH content of the spilled plastic, we compared our results to the PAH content measured and reported in the literature from 19 studies of plastic pellets (317 data points) and 15 studies of plastic debris (198 data points) found globally in the marine environment (Figure ). ,, When they arrived onshore on May 25, 2021, the white nurdles had an EPA16 PAH content (∼1260 ng/g) double the median for nurdles found globally in the marine environment (∼589 ng/g). It should be noted that many of these other studies examined nurdles with a yellowness index of 30 to 50, assuming that the yellowing indicated that these nurdles had been in the environment long enough to accumulate significant amounts of PAHs .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of PAH content for the plastic spilled during the M/V X-Press Pearl disaster analyzed in this study and plastic found in the ocean globally. Ranges of pollution level are those defined according to Yeo et al Data presented for the nurdles and plastic debris were collated from literature-reported absolute, mean, or median values, ,, details of which are available in Table S13. A comparison of each study is included in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the use of PAH-containing plasticizer/extender oils or carbon black, which are added during the production of rubber or elastomers to provide the materials with different mechanical and process-related properties (BfR 2009). Also, EPS contains non-intentionally added PAHs, with the highest anthracene levels in new EPS, likely from production (Yeo et al 2022). Apart from production, PAHs can also absorb to PS during use (Li, Ni, and Zeng 2017).…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…Given this increase in consumption and considering that toxic resources have been used in the manufacturing, use, and disposal process of EPS, some countries have regulated the manufacturing process. In contrast, others, such as the United States, have prohibited or restricted its use as food packaging [14][15][16]. These measures have undoubtedly made it easier to reduce the amount of production; however, they do not solve the problem since, according to the data previously presented, except in Asia, the consumption of products destined for food packaging represents little more than 30% of total consumption, leaving pending the integral management of the remaining 70% [17,18].…”
Section: Introductionmentioning
confidence: 99%